The effects of total quality management practices on sustainable performance: perspective from Malaysia - Kit Yeng, Sin; Muhammad Shahar, Jusoh; Choon Ling, Sim (Inderscience Enterprises Ltd., 2022)
This study seeks to investigate the relationship between total quality management (TQM) practices and sustainable performance. Data were collected from 4- and 5-stars hotels in Malaysia from June to December 2018. Based on a sample of 121 valid responses, empirical results indicate that TQM practices have significant and positive impacts on sustainable performance, encompassing economic performance, environmental performance and social performance. These practices could be considered as critical quality management practices that significantly contribute to sustainability goals. This study enriches the literature on quality management and sustainability management, as well as provides some important insights into the effective allocation of resources to achieve sustainable development goals.